Caring for the Transgender Individual. (September 2016) - Sedlak, Carol A.; Veney, Amy J.; Doheny, Margaret O'Bryan
Abstract : Issues about transgender individuals (TIs) as a disparate population are now being more openly discussed in the general public. However, healthcare providers often express feeling uncomfortable in interacting with TIs because they have not been educated about care of TIs and often base their care on insensitive stereotyping. The purpose of this informational article is to provide a foundation of knowledge for nurses and healthcare professionals for providing competent patient-centered care for TIs. Topics discussed include a description of the transgender population, commonly used terms to describe TIs, health risks and healthcare needs of TIs, and how to provide quality healthcare for TIs.